ANALISIS PENGARUH RASIO LIKUIDITAS TERHADAP RETURN SAHAM (Studi Pada Perusahaan Indeks LQ 45 Yang Terdaftar Di Bursa Efek Indonesia) - Yulia Yulia (Jurnal Khatulistiwa Informatika, 2016)
Along with rising Investment traded on the Indonesia Stock Exchange Capital Market, need for information For investors planning to invest Also Yang Increasingly increase. To facilitate the review under common control information Regarding The price index reflects price movements under common control, the Indonesia Stock Exchange price index 11 operates under common as prayer one guidelines For investors to invest in the market review modal.Indeks LQ 45 is a prayer One index of the 11 types The index issued by Bursa Securities Indonesia. LQ 45 Index is an index of 45 operates under common of a company under common control was recorded and is traded on the Indonesia Stock Exchange Yang has liquidity and capitalization fence between High in Top. under common control under common investor to invest on is to review benefit hearts Investment Management Context Level referred to as the advantage return.Return expected rate of return The anticipated an investor in the future. Meanwhile, back happens or the actual return is the rate of return investors lead in Financial. Liquidity Ratio indicates the Company's ability to meet financial obligations review The Right Short Term on Time. The indicator which was used to calculate the liquidity ratio review Used hearts Singer Research That current ratio, current ratio because The singer is a ratio comparing Assets with Debt is not smooth, so that the ratio singer is considered particularly important to review the Short-term creditors.